Comparison of Different Foam Rolling Protocols on Ankle Range of Motion, Strength, Muscle Activation, and Jump Performance. (2022) - Soares, Enrico Gori; Almeida, Vinícius Martins; Jesus, Henrique Barbosa de; Vasconcelos, Christine Megumi Wakuda de Abreu
No abstract available